2020
DOI: 10.1016/j.heliyon.2020.e03503
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of risk preferences and coping strategies to manage with various agricultural risks: evidence from India

Abstract: The present study proposes to analyse farmers' attitudes towards risk and examine the effect of specific sociodemographic and socio-economic characteristics on farmers' risk attitudes in irrigated and rain-fed regions of Odisha, India. A total of 400 randomly selected farmers participated in the experiment. The study applies the Modified Holt and Laury Lottery method for measuring risk attitudes. The majority of the farmers are having a risk-averse attitude and only a few farmers have a risk-taking attitude. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 44 publications
5
9
2
Order By: Relevance
“…Table 4 presents the results of the behavioral economic experiments on trust, risk, and time preferences (see Figure A6 in the Supporting Information for a graphical representation). Results of the risk preference experiment reveal that about 69% of the sampled farmers were risk‐averse, confirming the results obtained by other studies conducted in developing countries (Charness & Viceisza, 2016; Fischer & Wollni, 2018; Liebenehm & Waibel, 2014; Senapati, 2020; Ward & Singh, 2015). About 27% of the sampled farmers can be considered risk‐seeking, and about 3% were found to be risk‐neutral.…”
Section: Results and Disucussionsupporting
confidence: 86%
“…Table 4 presents the results of the behavioral economic experiments on trust, risk, and time preferences (see Figure A6 in the Supporting Information for a graphical representation). Results of the risk preference experiment reveal that about 69% of the sampled farmers were risk‐averse, confirming the results obtained by other studies conducted in developing countries (Charness & Viceisza, 2016; Fischer & Wollni, 2018; Liebenehm & Waibel, 2014; Senapati, 2020; Ward & Singh, 2015). About 27% of the sampled farmers can be considered risk‐seeking, and about 3% were found to be risk‐neutral.…”
Section: Results and Disucussionsupporting
confidence: 86%
“…Such a positive linkage may be due to unprecedented adverse weather conditions and plant diseases in these countries making farmers more likely to switch their crops. The finding is consistent with the study of Senapati (2020) which found that diverse crop varieties and short-term crops contribute to higher productivity and are less susceptible to climate shock.…”
Section: Resultssupporting
confidence: 92%
“…Access to improved crop storage facilities also has a positive effect on the TE of smallholder farmers, implying that lack of improved crop storage facilities is associated with a reduction in TE of about 16%. This may be attributed to the postharvest loss issue due to the use of traditional crop storage facilities, whereas access to improved storage facilities contributes to increased production and better quality of crops [59].…”
Section: Te Scores Of Smallholder Farmers By Farm System Typesmentioning
confidence: 99%